Anaerobic bacteria Cetobacterium sp. nov C33 plays a crucial role in the intestinal microbial balance and regulation of gene expression to immune and metabolic responses in Nile tilapia - Mario Andrés Colorado Gómez; Javier Fernando Melo-Bolívar; Ruth Yolanda Ruíz Pardo; Howard Junca; Juan F. Alzate; Luisa Marcela Villamil Díaz (PLoS ONE, 2026)
Aquaculture ranks among the largest global food production industries, with Nile tilapia ( Oreochromis niloticus ) being one of the most widely farmed species. However, increasing consumer demand and higher stocking densities place considerable stress on aquaculture systems, often leading to a rise in fish diseases. Probiotics have emerged as valuable tools in this sector, promoting fish health by modulating physiological functions such as metabolism, digestion, immune responses, stress tolerance, and disease resistance. Here, the probiotic potential of Cetobacterium sp. nov C33, an anaerobic bacterium isolated from the intestine of Nile tilapia, was evaluated on short-term dietary supplementation in fingerlings in laboratory conditions. Using 16S rRNA amplicon sequencing, we assessed the impact of Cetobacterium sp. nov C33 on gut microbiota, while transcriptomic analysis of the head kidney provided insights into immune system modulation. Results indicate that dietary inclusion of this anaerobic bacterium significantly alters the gut microbiota structure in tilapia fingerlings and regulates genes associated with key metabolic pathways, including the immune system, underscoring its potential as a probiotic for enhancing tilapia health. Our results offer promising evidence of its potential as a probiotic to improve tilapia health.